Graphitic Carbon Nitride Platforms Modified with Gold-Aryl Nanoparticles for Efficient Electrocatalytic Hydrogen Evolution. Issue 4 (4th July 2022) - Parambath, Javad B.M.; Hussain, Najrul; Alawadhi, Hussain; Park, Yeji; Dionysiou, Dionysios D.; Han, Changseok; Mohamed, Ahmed A.
ABSTRACT: Electrocatalytic hydrogen evolution reactions (HER) offer an enduring strategy for hydrogen fuel production and are vital for sustainable energy conversion and storage. To explore efficient and durable HER electrocatalysts, we fabricated gold-aryl nanoparticles (AuNPs-COOH) anchored on graphitic carbon nitride (g-C3 N4 ) sheets by reducing aryldiazonium tetrachloroaurate(III) salt with sodium borohydride at room temperature in water. Two different nanocomposites, AuNPs-COOH-g-C3 N4 (H) (higher amount of g-C3 N4 ) and AuNPs-COOH-g-C3 N4 (L) (lower amount of g-C3 N4 ) were prepared. Contact angle measurements revealed that the increased surface wettability of the nanocomposites on glass and silicon wafer surfaces compared to pristine g-C3 N4 . Cyclic voltammetry, electrochemical impedance spectroscopy, double-layer capacitance, linear sweep voltammetry, and chronoamperometry measurements revealed that AuNPs-COOH-g-C3 N4 (L) displayed the best HER performance in 0.1 M H2 SO4 electrolyte. Overall, nanocomposites exhibited higher electrocatalytic activity compared to bare AuNPs-COOH and pristine g-C3 N4 in current density and onset potential values. The AuNPs-COOH-g-C3 N4 (L) nanocomposite offered an excellent electrocatalytic activity and displayed a current density of 53.4 mA/cm 2 at 0.72 V vs RHE, which is nearly twice compared to bare AuNPs-COOH of 33.1 mA/cm 2 . In addition, the nanocomposite showed the lowest onset potential of 0.14 V vs RHE compared to 0.26 V and 0.31 V for AuNPs-COOH-g-C3 N4 (H) and AuNPs-COOH, respectively.